KONSEP KEPEMIMPINAN POLITIK DALAM HADIS UMMUL HADIS: ANALISIS NILAI-NILAI KEPEMIMPINAN NABI - Fahril Hendrawan; Sri Mawaddah (CV. Denasya Smart Publisher, 2025)
Political leadership in Islam is closely related to the exemplary behavior of the Prophet Muhammad SAW, who was not only a messenger of revelation, but also a leader of the people in all aspects of life, including politics. The Hadith of Ummul Hadith, namely the hadith